Rasayana Drugs Promise Better Anti-Covid-19 Medications - Dimri, Mayank; Rajwar, Virbal Singh; Kush, Luv (Asian Journal of Pharmaceutical Research and Development, 2020)
COVID-19virus is a worldwide tragedy. The western research endeavors are trying to findout an effective medication against this virus. The rasayana drugs promise rewarding medications. Their phytochemicals were studied with scientific rationality against COVID-19 virus.